Crossing borders in the age of confessionalization: seventeenth‐century Italian travel writing on the North. Issue 4 (14th August 2019) - Raunio, Anu
Abstract: This article explores two Catholic travellers' experiences of what they considered exotic and heretic Scandinavia. It re‐examines religious border‐crossing on the so‐called 'reverse Grand Tour' in Francesco Negri's Viaggio settentrionale (1663) and Alessandro Bichi's Viaggio in Svezia (1696), together with Bichi's text on ars apodemica entitled Instruttione et avvertimenti necessari per far longhi viaggi tanto per mare che per terra. Analysing the role of religion and adaptation in early modern cross‐cultural encounters between the Catholic South and Protestant North, it will examine how religious differences were negotiated in the everyday encounters and practicalities of travel. The article will show how on a continent divided by deep confessional differences, information and cultural influences were still mediated, facilitated and ultimately accommodated through both personal contacts and everyday practices.